1982
DOI: 10.1016/0304-3959(82)90147-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing pain behavior: the UAB Pain Behavior Scale

Abstract: Review of the chronic pain literature reveals that there have been few systematic attempts to devise rating scales which reliably and/or validly quantify pain behavior. The UAB Pain Behavior Scale was designed so that it could be administered rapidly by a variety of pain team personnel without sacrificing interrater reliability. The scale is described along with initial reliability and validity data. A summary of its use with chronic pain patients is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
1
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(79 citation statements)
references
References 4 publications
0
75
1
3
Order By: Relevance
“…Axis III is used for somatic diagnoses. We also used a sixth variable with different aspects of pain: a pain behaviour scale [35], a visual analogue scale for measuring pain intensity, and a five-graded scale for rating degree of reduced ability to work because of pain [24]. In this study, we used only the VAS measure and the axes I-IV.…”
Section: Methodsmentioning
confidence: 99%
“…Axis III is used for somatic diagnoses. We also used a sixth variable with different aspects of pain: a pain behaviour scale [35], a visual analogue scale for measuring pain intensity, and a five-graded scale for rating degree of reduced ability to work because of pain [24]. In this study, we used only the VAS measure and the axes I-IV.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative approach is the evaluation of behavioral manifestations of pain. [16] [100] and investigators have demonstrated that observational methods of evaluating pain behaviors are psychometrically sound when used with the general population (e.g., acute pain, communicative patients with chronic lower back pain, and osteoarthritic knee pain) and that the behaviors are sensitive to treatment effects. [73] [121] The utility and validity of these approaches with cognitively impaired older adults, however, has yet to be determined.…”
Section: Observational Methodsmentioning
confidence: 99%
“…The Checklist of Nonverbal Pain Indicators is a modification of the UAB-PBS [100] tool involving patient observation at rest and during movement of six pain-related behaviors, including vocalizations, grimaces, bracing, rubbing, restlessness, and verbal complaints. [34] The tool addresses the unique needs of the demented population and shows preliminary validity and modest reliability with cognitively impaired older adults in the acute care setting; however, additional refinement and evaluation with larger samples in diverse settings is needed to determine its utility with the demented older adult in acute and chronic pain.…”
Section: Observational Methodsmentioning
confidence: 99%
“…Behavioural assessment was carried out with the use of the UAB Pain Behaviour Scale [4], a standardised instrument capable of assessing through direct observation the global behaviour of the patient [8]. The scale consists of 10 target behaviours, each of which contributes equally to the total score, providing a range of possible scores from 0 to 10.…”
Section: Monitoring and Data Collectionmentioning
confidence: 99%
“…Many of these actions can be objectively analysed, quantified [6][7][8][9][10], and compared with the description that the patients themselves reported regarding their pain experience [11,12].…”
Section: Introductionmentioning
confidence: 99%